MicroRNA-608 Promotes Apoptosis in Non-Small Cell Lung Cancer Cells Treated With Doxorubicin Through the Inhibition of TFAP4 - Wang, Yi-Fei; Ao, Xiang; Liu, Ying; Ding, Dan; Jiao, Wen-Jie; Yu, Zhuang; Zhai, Wen-Xin; Dong, Sheng-Hua; He, Yu-Qi; Guo, Hang; Wang, Jian-Xun (Frontiers in Genetics, 2019)
Lung cancer is the most commonly diagnosed type of cancer and the leading cause of cancer-associated death worldwide. MicroRNAs (miRNAs) are non-coding single-stranded RNA molecules of 20-25 nucleotides in length. Single nucleotide polymorphisms are a class of genetic variation in the human genome, which when present in miRNA genes are associated with the risk of developing cancer. This study aimed to identify whether the miRNA (miR)-608 polymorphism rs4919510 influenced the incidence of lung cancer, and to explore the underlying mechanisms of miR-608 in the pathogenesis of the disease. A total of 37 patients with non-small cell lung cancer (NSCLC) were selected to determine the expression levels of miR-608; 96 NSCLC patients and 136 cancer-free healthy controls were recruited to determine the incidence of miR-608 rs4919510 in lung cancer patients. Additionally, the impact of miR-608 on the expression of predicted target genes, cell migration, viability, proliferation and apoptosis was also assessed. We found that the presence of miR-608 rs4919510 did not affect the susceptibility of patients to NSCLC or the maturation of miR-608. miR-608 expression levels were found to be downregulated in NSCLC tissues. Furthermore, overexpression of miR-608 promoted doxorubicin-induced apoptosis in A549 cells by inhibiting the expression of transcription factor activating enhancer-binding protein 4 (TFAP4), and high expression levels of TFAP4 were observed in NSCLC tissues. Therefore, our results may provide valuable insights for the chemotherapeutical treatment of NSCLC.